2021
DOI: 10.3390/nano11113031
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Protein Nanotubes Based on the Bacteriophage vB_KleM-RaK2 Tail Sheath Protein

Abstract: We report on the construction of functionalized nanotubes based on tail sheath protein 041 from vB_KleM-RaK2 bacteriophage. The truncated 041 protein (041Δ200) was fused with fluorescent proteins GFP and mCherry or amidohydrolase YqfB. The generated chimeric proteins were successfully synthesized in E. coli BL21 (DE3) cells and self-assembled into tubular structures. We detected the fluorescence of the structures, which was confirmed by stimulated emission depletion microscopy. When 041Δ200GFP and 041Δ200mCher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The retention of enzymatic activity in nanostructures formed by fused recombinant proteins was also demonstrated in our previous study with a bacteriophage tail sheath protein derived from the vB_KleM-RaK2 bacteriophage, 31 confirming that proteinaceous nanotubes are a suitable carrier for enzymes.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The retention of enzymatic activity in nanostructures formed by fused recombinant proteins was also demonstrated in our previous study with a bacteriophage tail sheath protein derived from the vB_KleM-RaK2 bacteriophage, 31 confirming that proteinaceous nanotubes are a suitable carrier for enzymes.…”
Section: Resultssupporting
confidence: 74%
“…Our recent study has shown that the fusion of an amidohydrolase YqfB to a nanotube forming monomer 041Δ200 resulted in a 3-fold decrease in enzymatic activity. 31 Therefore, at least a partial impairment in the activity of SNAP-tag within the nanotubes can be anticipated, but there was sufficient binding of the fluorescent enzyme substrate to observe the nanotubes within the cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations